Personnel Reforms and Performance in Law Enforcement among Directorate of Criminal Investigations Officers in Kenya: The Moderating Effect of Technology - Margaret Awino Ong’ale; Merecia Anne Musundi Sirera; Judy W. Mwangi (Eastern African Journal of Humanities and Social Sciences, 2025)
Policing is vital to a society’s criminal justice system, ensuring law and order, crime prevention, and public safety while protecting citizens’ rights. In Kenya, the Directorate of Criminal Investigations (DCI) faces challenges in balancing these duties. This study examines how personnel reforms affect DCI officers’ performance, grounded in Peelian Principles. Using a mixed-method approach, it collected quantitative data via Likert-scale questionnaires from 5,383 DCI officers across eight regions, analysing performance impacts with SPSS for objective, generalisable results. Qualitative data from open-ended interviews provided deeper insights into experiences and challenges. The sample included 384 respondents (230 DCI officers, 154 civil society representatives, and Nyumba Kumi), selected through multistage sampling. Data collecting involved questionnaires, interviews with Regional Criminal Investigations Officers, and focus groups with civil society. Quantitative data was analysed using descriptive statistics, while qualitative findings were thematically analysed, offering a comprehensive view of reform effects on DCI performance. The study found that police reforms in Kenya focused on facilities, remuneration, and deployment. DCI performance improved due to ongoing fair recruitment reforms. Crucially, the analysis revealed that while personnel reforms independently influence performance (ẞ = 0.429, p = 0.000), their effect is significantly enhanced when complemented by technological reforms (ẞ = 0.245, p = 0.000). To improve DCI effectiveness, the government should equitably upgrade facilities nationwide, invest in digital tools for emerging crimes, and institutionalise regular infrastructure audits. Simultaneously, competitive, inclusive remuneration and transparent, skill-based deployment, guided by officer feedback and supported by trained supervisors, are essential for morale, trust, and performance.